Hidden Grief, Visible Grades: Components of Academic Functioning after Friendship Loss in Adolescents - Ríos, Juan Camilo; Fernández, Lucía (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore the emotional and academic consequences of friendship loss among adolescents, identifying the components of academic functioning most affected by the hidden grief of relational dissolution. Methods and Materials: A qualitative research design was employed, drawing on semi-structured interviews with 24 adolescents (ages 13–18) from Argentina who had experienced the loss of a significant friendship within the past two years. Participants were recruited through purposive sampling to ensure diversity in gender, school type, and academic performance levels. Interviews were conducted in Spanish, audio-recorded, transcribed verbatim, and analyzed using NVivo 14 software. Data collection continued until theoretical saturation was achieved. Thematic analysis, combining inductive and deductive strategies, was used to identify patterns across participants’ narratives. Credibility was enhanced through independent coding, constant comparison, and reflexive memoing. Findings: Four overarching themes emerged: (1) Emotional impact of friendship loss, encompassing grief, sadness, anger, loneliness, insecurity, and rumination; (2) Academic consequences, including declines in motivation, concentration, and performance, as well as paradoxical overinvestment in schoolwork; (3) Coping and adjustment strategies, ranging from seeking support and creative expression to maladaptive behaviors such as avoidance and substance use; and (4) Identity and future orientation, reflecting disrupted self-concept, cautiousness in future friendships, and eventual processes of resilience and growth. Conclusion: The study demonstrates that friendship loss in adolescence is a profound relational rupture with both emotional and academic consequences. Recognizing academic decline as a potential indicator of hidden grief may inform educational and counseling practices. Supporting adolescents in coping with friendship loss through adaptive strategies can foster both resilience and academic recovery.